The Impact Of Implementation A Competency-Based Training On Front Office Students' Assesment - Mustika, Amalia (2006)
This paper presents the findings of a five month research project that evaluated the effects that competency-based approaches have had on students' assessment on the impact of hotel-related with the institute of tourism or VET sector.